ISTRAŽIVANJE UTICAJA EMOCIONALNIH MOTIVATORA NA PONAŠANJE POTROŠAČA - Virijević Jovanović, Saša; Jošanov Vrgović, Ivana; Janovac, Tatjana (International Journal of Economic Practice and Policy, 2021)
Regarding the importance of psychological processes in the consumer behavior, the article examines the influence of emotional motivators on purchasedecisions in cosmetics industry. The empirical research was conducted from February to March 2020, on the sample of 125 respondents in Serbia. The participants answered the questions about the positive and negative emotions that occurred during the purchasing process. When defining the questionnaire, we started from the fact that emotions, which influence consumer behavior can be integral or incidental emotions. The aim of the study was to identify the emotions that have the strongest effect on consumers when purchasing cosmetic products. During the statistical data processing, the following techniques and methods were implemented: the descriptive statistical measures (frequencies and percentage, arithmetical midranges), the measures of variability, the correlation method. The survey indicated that the most dominant emotions that affect consumer purchasing decisions related to cosmetics products in the Republic of Serbia are positive emotions. The majority of respondents recognized hope as the most important emotion in their buying behavior.
Keywords: consumer behaviour; emotional motivators; purchasing; cosmetics industry; emotional buying